2019
DOI: 10.1016/j.ebiom.2019.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the host environment on the antitubercular action of pyrazinamide

Abstract: a b s t r a c tPyrazinamide remains the only drug in the tuberculosis pharmacopeia to drastically shorten first-line therapy from nine to six months. Due to its unparalleled ability to sterilize non-replicating bacilli and reduce relapse rates, PZA is expected to be irreplaceable in future therapies against tuberculosis. While the molecular target of PZA is unclear, recent pharmacokinetic studies using small animal models and patient samples have highlighted the importance of host metabolism and immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 120 publications
(151 reference statements)
3
10
0
Order By: Relevance
“…We observed condition-specific drug potencies consistent with previous reports, suggesting that the models we adapted for high-throughput drug response measurements may be predictive of outcomes in animals. For example, the activity of pyrazinamide in acidic and intracellular models and inactivity in the standard model (Table S2) was consistent with in vitro (45,46) and animal studies (47)(48)(49). We also observed pyrazinamide activity with lipid carbon sources, which has not been previously reported.…”
Section: Drug Combination Dose Response Measurementssupporting
confidence: 89%
“…We observed condition-specific drug potencies consistent with previous reports, suggesting that the models we adapted for high-throughput drug response measurements may be predictive of outcomes in animals. For example, the activity of pyrazinamide in acidic and intracellular models and inactivity in the standard model (Table S2) was consistent with in vitro (45,46) and animal studies (47)(48)(49). We also observed pyrazinamide activity with lipid carbon sources, which has not been previously reported.…”
Section: Drug Combination Dose Response Measurementssupporting
confidence: 89%
“…This leads to a lethal alteration of membrane permeability; however, the exact mechanism by which this occurs is not yet known (3). It is important to note that other recent studies found that extracellular acid pH is not required in order for PZA/POA achieve its lethal effect (4,5,6). This confirms that the real mechanism of action of PZA is actually more complicated than previously thought, and further research is required.…”
Section: Introductionsupporting
confidence: 62%
“…Drugs with well-established sterilizing potency included rifampin, bedaquiline, and pyrazinamide. Pyrazinamide was excluded from in vitro analysis because its full activity requires in vivo conditions 27 . The well-established non-sterilizing drugs examined included isoniazid, streptomycin, and ethambutol.…”
Section: Resultsmentioning
confidence: 99%